Quantifying neonatal pulmonary mechanics in mechanical ventilation. (July 2019) - Kim, Kyeong Tae; Knopp, Jennifer; Dixon, Bronwyn; Chase, Geoff
Highlights: NICU ventilation data set of 535, 428 breaths from 9 invasively ventilated NICU patients on conventional ventilation. A single compartment model successfully captures all observed dynamics and mechanics. NICU infants had 21% asynchrony rate, which was partly ventilation mode dependent. There were significant differences in elastance between difference weight groups, and those receiving surfactant therapy. Abstract: Background: Mechanical Ventilation (MV) is an important intensive care therapy. It is often used in neonatal intensive care units (NICUs) to treat respiratory distress syndrome. This paper uses model-based methods in a first in-depth attempt to quantify the underlying lung mechanics in NICU patients. Methods: Up to 24 h of airway flow and pressure data were recorded in 10 mechanically ventilated patients. A single compartment model with added term for the pressure drop across the endotracheal tube is used to identify breath-specific elastance and resistance. Result: The model was fitted to 422, 475 (79%) breaths of 535, 428, with the remainder comprising a range of asynchronies. Elastance was median 1.62 [IQR: 0.85–2.25] cmH2 O/ml and resistance 5.22 [0.00–33.85] cmH2 O.s/ml. Patients treated with surfactant therapy had significantly lower specific elastance (adjusting for weight) than those without (p ≤ 0.01). A decrease in elastance with increasing weight was also noted. Conclusion: The single compartment model was successfully fit with low error. The subgroup cohorts showed expected trends and further validates the identified model values. There was significant breath-to-breath variability in elastance within and between patients.